2005
DOI: 10.1124/mol.105.014662
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Increases Mitochondrial Efficiency and Reduces Oxidative Stress in Cerebral Blood Vessels

Abstract: We report here that estrogen (E(2)) modulates mitochondrial function in the vasculature. Mitochondrial dysfunction is implicated in the etiology of vascular disease; thus, vasoprotection by estrogen may involve hormonal effects on the mitochondria. To test this hypothesis, mitochondria were isolated from cerebral blood vessels obtained from ovariectomized female rats, with or without E(2) replacement. Estrogen receptor-alpha (ER-alpha) was detected in mitochondria by immunoblot and confocal imaging of intact v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

18
254
4
3

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 282 publications
(279 citation statements)
references
References 38 publications
18
254
4
3
Order By: Relevance
“…Overexpression of MnSOD results in neuroprotection by reducing cellular apoptosis and decreasing brain ischemic damage (Keller et al, 1998). Previously, we found that, in cerebrovascular mitochondria from female rats treated with estrogen, protein levels of MnSOD were increased (Stirone et al, 2005). In contrast, in the current study, a similar in vivo estrogen treatment had no effect on protein levels of MnSOD in female brain mitochondria.…”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation
“…Overexpression of MnSOD results in neuroprotection by reducing cellular apoptosis and decreasing brain ischemic damage (Keller et al, 1998). Previously, we found that, in cerebrovascular mitochondria from female rats treated with estrogen, protein levels of MnSOD were increased (Stirone et al, 2005). In contrast, in the current study, a similar in vivo estrogen treatment had no effect on protein levels of MnSOD in female brain mitochondria.…”
Section: Discussioncontrasting
confidence: 50%
“…Emerging evidence indicates mitochondria are a novel target of estrogen (Duckles et al, 2006;Nilsen and Brinton, 2004;Singh et al, 2006). We recently demonstrated in cerebral blood vessels of female rats that estrogen decreases mitochondrial H 2 O 2 production (Stirone et al, 2005). Estrogen also increased expression of several mitochondrial electron transport chain proteins, including cytochrome c and complex IV subunits, and increased complex IV and citrate synthase enzyme activities.…”
Section: Introductionmentioning
confidence: 99%
“…Some of the genes, such as annexin-1 and bcl-x, are known as estrogen-regulated genes (Castro-Caldas et al 2001, Stoltzner et al 2001. A few genes, including mitochondrial uncoupling protein 2 and platelet factor 4, which were regulated by E 2 in our study, have been previously described as estrogen insensitive in other tissues (Norris & Bonnar 1994, Luukkaa et al 2001, Stirone et al 2005. We also detected transcriptional changes in a number of genes, which have not been reported to be estrogen-regulated (leukocyte 12-lox, STAT6, and a-parvin).…”
Section: Discussionmentioning
confidence: 98%
“…Similarly, LPS and TNF increase NRF-1-regulated Tfam gene expression and subsequent increases in mtDNA-encoded COI and NDI mRNA, reflecting mitochondrial transcriptional activity befitting reports that LPS exposure doubles COI mRNA content in mouse cells . Following NRF-1 production, Tfam levels and mtDNA copy number also increase, which is necessary to support the capacity for oxidative phosphorylation (Scarpulla, 2008) and which might reduce oxidative stress (Stirone et al, 2005).…”
Section: Discussionmentioning
confidence: 99%